Pengaruh Informasi Musisi, Visual Stage Act, dan Daya Tarik Lagu pada akun Instagram @trafficjammusic terhadap Keputusan Pembelian Tiket Konser - Irenea Gendis; Aulia Suminar Ayu (Universitas Sebelas Maret (UNS), 2026)
This research explores the influence of musician information, stage act visuals, and song appeal in Instagram content posted by @trafficjammusic on audiences’ concert ticket purchase decisions. In the digital era, social media—particularly Instagram—serves as a persuasive communication platform through visual content, playing a key role in shaping consumer behavior. The study is grounded in the Elaboration Likelihood Model (ELM), which explains how individuals process persuasive messages via central and peripheral routes. This is an explanatory quantitative study using survey data collected through online questionnaires from 98 followers of the @trafficjammusic Instagram account. The variables tested include musician information (central route), stage act visuals, and song appeal (both peripheral cues). Data were analyzed using partial, simultaneous, and multiple regression tests. Findings indicate that musician information and song appeal significantly and positively influence concert ticket purchase decisions. In contrast, stage act visuals showed a significant but negative impact, suggesting that even when visual performance is less prominent, audiences still tend to purchase tickets—likely due to emotional engagement and fan loyalty. Simultaneously, all three variables collectively have a significant and positive influence on purchase decisions. This study contributes to understanding how digital music promotion works through audience message elaboration and highlights the strategic role of informative and emotionally resonant content in independent music marketing. Practically, it recommends focusing on accurate musician information and catchy song content, while nurturing community engagement as a long-term asset.